The relationship between abusive supervision and organizational trust: The role of subordinates self-esteem - Velez,Maria João (2020)
Interest in abusive supervision (Tepper, 2000) has increased due to its serious personal and organizational costs. As such, there is a need for additional studies that identify the individuals factors that can minimize the adverse effects of abusive supervision. Specifically, we predict employee self-esteem as a buffer of the relationship between abusive supervision, organizational trust and in-role behaviors. Additionally, we suggest organizational trust as a possible mechanism linking abusive supervision to in-role behaviors. Our model was explored among a sample of 201 supervisor-subordinate dyads from different organizational settings. The results of the moderated mediation analysis supported our hypotheses. That is, abusive supervision was significantly related to in-role behaviors via organizational trust when employees self-esteem was low, but not when it was high. These findings suggest that self-esteem buffers the impact of abusive supervision perceptions on organizational trust, with consequences for performance.